'Big Data in Nurse Education'. (April 2017) - Schwerdtle, Patricia; Bonnamy, James
Highlights: Description of big data in relation to nurse education. Discussion of the potential of big data in this context, barriers to implementation and the potential dangers. Recommendations to integrate this exciting new possibility to inform best practice in nurse education.